Produção e caracterização de curativo biopolimérico impregnado com carvão ativado e extrato natural de noz-pecã - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Skin dressings are responsible for accelerating the healing process, preventing inflammation and scarring, especially when they have bioactive compounds in their composition, increasing this prevention. In this sense, the objective of the present work was to develop a biopolymeric dressing from gelatin containing activated carbon (AC) impregnated with pecan nut shell extract to add antioxidant properties to the material. The experimental methodology consisted of the development of the extracts by the maceration method and their characterization regarding the presence of phenolic compounds and antioxidant properties; impregnation of AC with bioactive compounds present in the extract, obtaining impregnated activated carbon (IAC); development of membranes containing gelatin (MG), gelatin and CA (MAC), gelatin and extract (ME) and gelatin and IAC (MIAC); finally, the produced membranes were characterized regarding thickness, mechanical properties, water vapor permeability (WVP) and water vapor transmission rate (WVTR), swelling, solubility, Fourier transform infrared spectroscopy (FTIR) and thermal gravimetric analysis (TGA). The results obtained in the characterization of the extracts were 1483,04 mgGAE g-1 for phenolic compounds, 5515,61 µMFe g-1, and 38,94 % for antioxidant activity by the FRAP and DPPH methodologies, respectively. The values obtained for thickness, elongation at break, and tensile strength were 0,44 mm, 80,76 %, and 0,38 MPa for MG, 0,47 mm, 93,91 %, and 0,07 MPa for MAC, 0,47 mm, 85,86 % and 0,09 MPa for MIAC, and 0,35 mm, 100,85 % and 0,08 MPa for ME, respectively. The WVP and WVTR values obtained were 2,36 g m-2 d -1 Pa-1 and 187,58 g m-2 d -1 for MG; 2,60 g m-2 d -1 Pa-1 and 194,18 g m-2 d -1 for MAC; 2,52 g m-2 d -1 Pa-1 and 188,43 g m-2 d -1 for MIAC; and 2,15 g m-2 d -1 Pa-1 and 210,29 g m-2 d -1 for ME. The solubility of the membranes varied between 87,03% for MG, 84,96% for MAC, 84,36% for MIAC, and 85,65% for ME. The highest swelling index was obtained for the ME membrane after 24 h, with a value of 251.59 %. The FTIR analysis indicated the presence of groups related to gelatin, glycerol, and phenolic compounds in the extract. The TGA analysis indicated that the additives increased the thermal stability of the materials. According to the results obtained, it can be confirmed that the pecan nut shell extract has a high content of phenolic compounds and antioxidant capacity, which can help in the healing process. In addition, the materials produced have physical and chemical characteristics necessary for the application as a dressing. Therefore, further studies are indicated to analyze other properties of the membranes.
Keywords: Gelatina; Tratamento de feridas; Compostos bioativos; Propriedades antioxidantes; Gelatin; Wound treatment; Bioactive compounds; Antioxidant Properties; CNPQ::ENGENHARIAS